Hypomagnesaemia among patients with type 2 diabetes mellitus and impaired glucose tolerance and its correlation with glycemic control: a cross-sectional study in a tertiary care hospital of Bangladesh - Mahin, Tasnova; Rahim, Muhammad Abdur; Haque, Wasim Md Mohosinul; Qader, Md Abdul; Faria, Labeeba (BIRDEM Medical Journal, 2022)
Background: Hypomagnesaemia is linked to insulin resistance in type 2 diabetes mellitus (T2DM) and chronic diabetic complications. Prevalence of hypomagnesaemia is high in patients with T2DM and multiple studies have shown evidence of effect of serum magnesium (Mg) level on glycaemic control in these patients. The aims of this study were to evaluate the frequency of hypomagnesaemia in hospitalized patients with T2DM and impaired glucose tolerance (IGT) and to evaluate its correlation with glycaemic control. Methods: This was a cross-sectional study conducted from November, 2016 to March, 2017 in BIRDEM General Hospital. Hypomagnesaemia was defined as serum Mg concentration <0.7 mmol/L. Patients who had acute diarrhea or vomiting in previous 7 days, patients who had chronic diarrhea or malabsorpsion syndrome or who had recent history of taking diuretics were excluded from the study. Patients’ clinical information were collected using a structured questionnaire and laboratory information were collected from the hospital records. Results: Total patients were 100, including T2DM (92) and IGT (8). Thirty nine (42.4%) patients with T2DM and five (62.5%) patients with IGT had hypomagnesaemia. The median (IQR) serum Mg level in patients with T2DM was 0.77 (0.6-0.8) mmol/L and IGT was 0.6 (0.52-0.77) mmol/L. HbA1c was higher among patients with hypomagnesaemia than normal Mg level [median (IQR) 9.4 (7.8-12.7) % vs 8.85 (7.2-9.95) %] though it was not significant (p>0.05). The mean fasting blood glucose (FBG) was 9.82 mmol/l in patients with hypomagnesaemia and 9.63 mmol/l in patients with normal serum Mg. Median 2-hour post prandial blood glucose level was 12 (10.4-16.15) mmol/L in hypomagnesaemia group and 11.7 (10.3-14.7) mmol/L in normal Mg group, though the difference was not statistically significant. There was negative correlation between serum Mg and HbA1c, FBG and post prandial blood glucose level (r, -0.075, -0.003. -0.006 respectively). Among the patients with hypomagnesaemia, the percentage of ischemic heart disease (IHD), diabetic retinopathy, diabetic nephropathy and diabetic neuropathy was 31.8%, 36.4%, 43.2% and 34.1% compared to 23.2%, 30.4%, 32.1% and 25% respectively in patients with normal Mg level. Conclusion: Around half of the patients with T2DM and IGT had hypomagnesaemia and patients with hypomagnesaemia were found to have relatively poor glycemic control and had increased rate of diabetic complications. Although relationship between serum magnesium level and glycemic control was not significant, it indicated the need of further research in this aspect. BIRDEM Med J 2022; 12(3): 207-211